Shedding kinetics of soluble tumor necrosis factor (TNF) receptors after systemic TNF leaking during isolated limb perfusion. Relevance to the pathophysiology of septic shock. - Aderka, D (1998)
We examined the kinetics of shedding of the soluble TNF receptors (TNF-Rs) in response to TNF leakage during isolated limb perfusion procedures and correlated them to the resulting hemodynamic effects. Shedding of the TNF-Rs started 7 min after TNF leakage into the systemic circulation. Three waves of shedding were observed peaking at 1, 8-12, and 48-72 h both in vivo and in cell cultures. The soluble receptors prolonged the half-life of TNF in the systemic circulation to 2.5-6 h. Excess shedding of the p75 compared with p55 TNF-Rs was noted during the first wave. The amount and speed of shedding of the p75 TNF-Rs were proportional to the serum TNF levels (P < 0.001). A maximal shedding capacity was attained only during the first wave of shedding, at TNF concentrations of approximately 1.5 ng/ml. Above this level, the linearity between TNF and its soluble receptors was lost. TNF-induced hypotension coincided with the initial imbalance between the concentrations of TNF and its soluble receptors. Despite the spontaneous correction of this imbalance at 8-12 h, the hemodynamic and biochemical alterations persisted and were further aggravated at 18 h, suggesting that other factors induced earlier by TNF are responsible for the perpetuation of the hemodynamic instability. This study may provide the basis for a more physiological therapeutic approach to TNF neutralization in septic shock patients.